(Expected difficulties with) density-profile control in W7-X high-performance plasmas. (31st August 2018) - Beidler, C D; Feng, Y; Geiger, J; Köchl, F; Maßberg, H; Marushchenko, N B; Nührenberg, C; Smith, H M; Turkin, Y
Abstract: For strong central heating the interdependency of the particle and energy balances is invoked to show that the particle source required for steady-state conditions is related to the power deposition through the ratio of particle to energy fluxes. Consequences of this relationship for high-performance plasmas in the Wendelstein 7-X (W7-X) stellarator are investigated for long-pulse scenarios in which only electron cyclotron resonance heating is employed. If neoclassical transport is predominant in the core region, as is demonstrated to have been the case for comparable plasmas in the previous experiment, Wendelstein 7-AS, then hollow density profiles are shown to be inevitable in W7-X given the expected recycling properties of the device and the refueling capabilities of the present pellet-injection system.